The role of trust in the resource allocation process of an old university - Melina M. Manochin (International Journal of Economic Sciences and Applied Research, 2008)
The issue of effective management accounting systems, and especially the resource allocation procedures, have attracted considerable interest among higher education institutions in recent years. Relevant previous research indicates that several universities adopt different approaches to the resource allocation problem, employing models and procedures that reflect their organisational arrangements and their internal socio-political dynamics. We argue that while studying accounting processes in their organisational context, the role of trust should also be considered carefully. In particular, it is very important to consider the attitudes of the individuals involved and interacting within organisational processes, and especially the trust between them, which plays an important role to the overall good governance of these processes. In our study, the role of interpersonal trust in an old Scottish University resource allocation process is examined. The study indicates that trust is a very necessary insight to the facilitation of social structures of accountability that enhance a better governance of the resource allocation process.
Keywords: M41; D73; I20; 330; organisational trust; universities; resource allocation; organisational context of accounting